2021
DOI: 10.1080/01441647.2021.1979689
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic impact assessments of high-Speed rail: A meta-Analysis

Abstract: The interest in the socioeconomic impact assessments of the highspeed rail (HSR) system is burgeoning as many countries are considering investing in such a system. While extensive studies have provided a wide range of evaluations of HSR on the socioeconomic impact, primarily from an ex-post perspective, it remains unclear how reliable the evaluation outcomes were, given the variety of data, method and research framework being adopted. This paper provides a comprehensive review of the socioeconomic impact studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…We draw our analytical framework of socio‐economic impact from Cheng and Chen (2022). This meta‐analysis, by analysing 242 academic publications, is by far one of the most comprehensive assessments of railway projects' socio‐economic impact.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We draw our analytical framework of socio‐economic impact from Cheng and Chen (2022). This meta‐analysis, by analysing 242 academic publications, is by far one of the most comprehensive assessments of railway projects' socio‐economic impact.…”
Section: Methodsmentioning
confidence: 99%
“…Conceptual model for SGR socio‐economic impact assessment. Source : Adapted from Cheng and Chen (2022) based on Kenyan SGR analytical needs…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, 356 responses would be needed from both intervention and control cohorts at each of two time points for the same power from this analysis framework. As the recruitment target is 1,200 participants per group per HS2 Phase (n = 4,800 in total), and 600 participants per group for the part of the route not proceeding as planned (1,200 in total) the study will be well-powered to detect a meaningful difference in the primary outcome using a DiD framework, and separate analyses for Phases 2a and 2b will be feasible. 3.…”
Section: Cohort Datamentioning
confidence: 99%
“…A recent metaanalysis found that the majority of studies investigating the impact of high-speed rail system developments have focused on changes in accessibility, modes of transport, the environment, tourism, housing or land, labour market, and economic performance [1]. Very limited consideration has been given to health impacts, particularly impacts on mental health and wellbeing [1,2]. Transport infrastructure, such as railways, can create physical or psychological barriers in the local community that impact health and wellbeing by disrupting social connectedness, reducing opportunities for exercise, and reducing accessibility to local health services and supermarkets with healthy food options [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, high-quality connections to HSR bring new agglomeration effects to centres (e.g., Ahlfeldt and Feddersen, 2018, in the case of the German cities of Cologne and Frankfurt am Main). A recent overview of the socio-economic impacts of HSR is provided by e.g., Cheng and Chen (2022).…”
Section: Introduction and General Framework Of The Analysismentioning
confidence: 99%